Visualisation forms in passive sonar with towed array - Raganowicz, A.; Kilian, L.; Marszal, J.; Ostrowski, Z.; Schmidt, A. (Archives of Acoustics, 2006)
This paper presents forms of visualisation used in modern underwater systems, a topiccovered at two previous Seminars. This year’s presentation describes how imaging is organisedon the monitors of a passive sonar with a long acoustic array, towed behind the ship’sstern, part of a modernisation project at the Department of Marine Electronics Systems. Theintroduction gives an overview of the design of the sonar and the type of signals received andused for imagining. The article then describes the other factors, which are important for howimages are organised, i.e. the operators’ tasks, the settings and how they are presented, otherdata from additional sonar sensors, how the systems works with the other on-board systems,operator training and ergonomics. Examples of images are included.